1999
DOI: 10.1046/j.1365-4362.1999.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative estimation and recommendations for supplementation of protein lost through scaling in exfoliative dermatitis

Abstract: ED may increase the daily protein loss by approximately 25-30% in psoriasis and 10-15% in other causes. Standard treatment for ED and protein supplementation based on our recommendations can minimize the adverse effects of a negative nitrogen balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 28 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…[7] Hypoproteinemia could be due to protein loss through scaling, chronic malnutrition, or dilution due to hypervolemia. [1116] Elevated levels of blood urea and serum creatinine were seen in two (6.6%) patients who were also known diabetics; pre-existing diabetes could be the cause for this finding. In study by Rafael et al ., increased serum creatinine was observed in 41% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Hypoproteinemia could be due to protein loss through scaling, chronic malnutrition, or dilution due to hypervolemia. [1116] Elevated levels of blood urea and serum creatinine were seen in two (6.6%) patients who were also known diabetics; pre-existing diabetes could be the cause for this finding. In study by Rafael et al ., increased serum creatinine was observed in 41% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…showed that daily protein loss increased by 25-30% in psoriatic erythroderma and 10-15% in non-psoriatic erythroderma. [11] Previous studies have shown that generalized erythema and scaling are the most common findings, seen in up to 100% of cases. [56] In a study by Pal, scaling was seen in 84.4% of cases[4] and in an Indian study, scaling in 100% and erythema in 80% of cases was observed.…”
Section: Discussionmentioning
confidence: 99%
“…General measures for a case of erythrodermic psoriasis (Burden & Kirby, ; Cuellar‐Barboza et al, ; Kanthraj et al, ; Mistry, Gupta, Alavi, & Sibbald, ; NICE, ; ; Rothe, Bernstein, & Grant‐Kels, ; Shepherd, )…”
Section: Treatment Strategies For Specific Types Of Psoriasismentioning
confidence: 99%
“…It is estimated that patients of erythrodermic psoriasis have 25% increase in the daily protein loss (in scales) equivalent to 22.5 g which may result in hypoalbuminemia and negative nitrogen balance if not corrected. The daily protein intake should be increased by 25–30% above the normal balanced diet content which is 56 g for men, 44 g for women and 34 g for children (Kanthraj et al, ).…”
Section: Treatment Strategies For Specific Types Of Psoriasismentioning
confidence: 99%
“…Protein loss in the form of desquamation and exudation is significant, resulting in hypoproteinemia. The daily loss of scales increases from 500-1000 mg to 20-30 g (1,14). Typically, there is hypoalbuminemia with a relative increase in immunoglobulins, especially γ-globulins.…”
Section: Pathogenesismentioning
confidence: 99%